PARTNERSHIP PROGRAM SYSTEM TROUGHT SI BULE ALBINO INSTITUTIONAL BUSINESS BY MINE FIRM IN BINUANG DISTRICT KAB. TAPIN - Ali Khamdan (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2016)
This research explains how the partnerships system built between the comunnities arround the mine with coal mining company. Citizens fostered independence catfish farm business trought programs binuang original catfish farming system (si Bule Albinoe), the company manages CSR citizens trought funds managed by LPB Baprida. This study used descriptive qualitative approach, data are obtained primarily trought interviews with the target group, secondary data obtained from LPB Baprida. The result showed ; 1) system partnership undertaken by the company has been very precisely so as to increase income of farmers catfish. 2). a huge market demand of the catfish into opprtunities by catfish farmers in the cultivation development. 3). expand the marketing network of catfish up to the modern market. 4) in the development catfish farming is often monopolized by midlemen so that advantage by catfish farmers againt reduced. This may affect the interest of farmers in developing catfish, but the market demand for the development of this very large catfish.